Neoplasia sólida pseudopapilar del páncreas (Revista Argentina de Cirugía, 2021)
Background: Solid Pseudopapillary Neoplasia (NSSP) pancreas is a rare pancreatic tumor commonly found in young women. They are usually not very symptomatic and the prognosis is good in resective surgery.Objective: to describe 6 cases from 3 different centers and to make an updated review of the topic.Materials and methods: analysis of clinical histories, biopsies and surgical protocols. Period from January 2014 to April 2017.Results: we found 6 cases, with 5 women and 1 male; the mean age was 39.7 years (range 28 to 54 years). In 3 cases we dealt with incidental findings. In all cases, echography and CAT were used for the diagnosis and in 2 cases, MRI was performed. All tumors were found in the body and / or tail of the pancreas. In 2 surgeries a videolaparoscopic approach was performed, the mean surgical time was 91.17 minutes and the mean number of days of hospitalization was 5.5, with 3 patients reentered for postoperative complications (one abscess and two pancreatic fistulas).Conclusions: these tumors are rare; however we believe that the advances in imaging methods will increase the diagnosis and treatment of this pathology so that its incidence will increase. We want to emphasize the importance of the videolaparoscopic approach for this type of pathology since in most cases it is feasible with good results. These surgeries should be performed in a center where their complications can be managed to avoid reinterventions.
Keywords: Frantz tumor; pancreatic pseudopapillary neoplasm; cystic neoplasm of the pancreas; videolaparoscopic pancreatectomy; pancreatic fistula